Role of Combined Lipoic Acid and Vitamin D3 on Astrocytes as a Way to Prevent Brain Ageing by Induced Oxidative Stress and Iron Accumulation. (28th February 2019) - Molinari, Claudio; Morsanuto, Vera; Ghirlanda, Sabrina; Ruga, Sara; Notte, Felice; Gaetano, Laura; Uberti, Francesca
Abstract : Brain ageing is a complex multifactorial process characterized by gradual and continuous loss of neuronal functions. It is hypothesized that at the basis of brain ageing as well as age-related diseases, there is an impairment of the antioxidant defense system leading to an increase of oxidative stress . In this study, two different biological aspects involved in brain ageing and neurodegeneration have been investigated: oxidative stress and iron accumulation damage. In primary mouse astrocytes, the stimulation with 50 μ M lipoic acid (LA) and 100 nM vitamin D (vitD) was first investigated in a time-course study to determine the dosages to be used in combination and then in a permeability test using an in vitro blood-brain barrier. In a second set of experiments, the role of oxidative stress was investigated pretreating astrocytes with 200 μ M H2 O2 for 30 min. The ability of vitD and LA alone and combined together to prevent or repair the damage caused by oxidative stress was investigated after 24 h of stimulation by the MTT test, mitochondrial membrane potential measurement, and Western blot analysis. To induce neurodegeneration, cells were pretreated with 300 μ M catalytic iron for 6 days and then treated with vitD and LA alone and combined for additional 6 days to investigate the protection exerted by combination, analyzing viability, ROS production, iron concentration, and activation of intracellular pathways. In our study, the combination of LA and vitD showed beneficial effects on viability of astrocytes, since the substances are able to cross the brain barrier. In addition, combined LA and vitD attenuated the H2 O2 -induced apoptosis through the mitochondrial-mediated pathway. The combination was also able to counteract the adverse conditions caused by iron, preventing its accumulation. All these data support the hypothesis of the synergistic and cooperative activity exerted by LA and vitD in astrocytes indicating a possible new strategy to slow down ageing.